2020
DOI: 10.1186/s13075-020-02291-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine levels in patients with systemic lupus erythematosus: whole blood is preferable but serum levels also detect non-adherence

Abstract: Background Hydroxychloroquine (HCQ) levels can be measured in both serum and whole blood. No cut-off point for non-adherence has been established in serum nor have these methods ever been compared. The aims of this study were to compare these two approaches and determine if serum HCQ cut-off points can be established to identify non-adherent patients. Methods HCQ levels were measured in serum and whole blood from 573 patients with systemic lupus erythematosus (SLE). The risk factors for active SLE (SLEDAI sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 32 publications
(50 reference statements)
2
28
0
Order By: Relevance
“…This model was also used for simulations of the serum concentrations serum PK data including data from 20 patients from the Gautret et al study 6 with a serum/whole blood correction ratio of 0.53 20 . The patients in the Gautret et al study were confirmed COVID‐19 and received 200 mg every 8 hours for 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…This model was also used for simulations of the serum concentrations serum PK data including data from 20 patients from the Gautret et al study 6 with a serum/whole blood correction ratio of 0.53 20 . The patients in the Gautret et al study were confirmed COVID‐19 and received 200 mg every 8 hours for 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…However, one of the major shortcomings of these studies is the lack of validated methods for measuring blood levels of drugs and their metabolites, and the lack of comprehensive evaluation of the relationships between these levels and clinical parameters. Although a few studies in SLE, RA patients have shown that hydroxychloroquine as well as its metabolites have significant effects on treatment efficacy and adverse effects, there is no comprehensive study on this subject (Jallouli et al 2015b ; Omri et al 2020 ; Blanchet et al 2020 ; Carlsson et al 2020 ; Munster et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Monte Carlo simulations were performed using NONMEM software, version 7.3 (Icon Development Solutions, Ellicott City, MD, USA). This model was also used for simulations of the serum concentrations serum PK data including data from 20 patients from Gautret et al study [6] with a serum/whole blood correction ratio of 0.53 [16]. Gautret et al study patients were confirmed COVID-19 and received 200 mg every 8 hours during 10 days.…”
Section: Population Pharmacokinetic Modelling and Simulationmentioning
confidence: 99%